#TITLE_ALTERNATIVE# - HANIF SANTYABUDHI ( NIM :12910020),
Sedimentation is a phenomenon that often occurs in coastal areas. Spatially and temporally information about sediment concentrations are needed to understand this phenomenon. However, in-situ measuring sediment instruments that has been available is not capable of providing a long time series data so hydro-acoustic is used. The method used in this study was adapted from Deines (1999) and Gartner (2002) based on the relationship of proportionality between the intensity of the acoustic return signal with suspended sediment concentration. Empirical equations were obtained and then the equation evaluated through the calibration process between the two parametersBackscatter intensity in Tanjung Gondol waters is about 28 counts to 90 counts. The intensity is strengthened with depth increasing. After the signal corrected, we obtained the equation: 10log10𝑆𝑆𝐶𝑆𝑆𝐶𝑟𝑒𝑓=0,6996∗𝐸𝐼−19,076 Value of SSCref is 7 mgL-1 and correlation coeficient is 0,87 with average error of 21,9 %.